2017
DOI: 10.1101/124636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ethics conundrum in Recall by Genotype (RbG) research: Perspectives from birth cohort participants

Abstract: would be most valuable and informative. Our findings highlight the importance of solidarity, reciprocity and co-production in biobank/participant relations, especially in long-term birth cohort studies where relationships develop over a lifetime. We argue that strong trusting relationships between study and participant confer great responsibility on researchers regarding duty of care. We make recommendations for conducting RbG research in longitudinal studies beyond those already available in the literature fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The ethical papers were mostly focused on the perspective of participants to RbG: authors investigated participants' understanding of the rationale of RbG-designed studies [15], the experience of participation in genetic research [15,19,20], the expectations associated with and the experience of recruitment in RbG studies [19,21], and the communication of individual genetic results (meanings of genetic results, disclosure) [15,[20][21][22][23] (Table 1).…”
Section: Identification Of Relevant Rbg Ethical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethical papers were mostly focused on the perspective of participants to RbG: authors investigated participants' understanding of the rationale of RbG-designed studies [15], the experience of participation in genetic research [15,19,20], the expectations associated with and the experience of recruitment in RbG studies [19,21], and the communication of individual genetic results (meanings of genetic results, disclosure) [15,[20][21][22][23] (Table 1).…”
Section: Identification Of Relevant Rbg Ethical Issuesmentioning
confidence: 99%
“…On the other hand, in population studies where RbG was not foreseen at the outset, re-call could be performed without revealing the main reason for it. While such an approach may appear unacceptable on principle, currently, there are no recognized ethical and legal standards for RbG in cohorts where RbG was not planned and which was therefore not included in the original informed consent [2,6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings here report on the participants' experiences and thoughts on how CO90s engaged with them and the resultant relationship and trust they developed for it. This kind of trust that participants develop for their longitudinal cohort studies has been mentioned elsewhere [37] including in other studies [38] such as the Irish Longitudinal Study of Ageing (TILDA) which reported that their participants felt they had a bond with the study and a special rapport with data collectors and that this impacted on participant retention [39]. Consistent with previous writings [40] we have evidenced here that cohort study participation should not be considered a unidirectional activity, the interviews reported here demonstrate that the perceived reciprocity contributed to sustaining the long-term commitment required for a longitudinal study.…”
Section: Discussionmentioning
confidence: 92%
“…ALSPAC's strict procedures of anonymity and confidentiality are made explicitly clear to participants [ 31 ]. Qualitative research reported participants were trusting and had faith in ALSPAC and ‘considered themselves part of the ALSPAC team’ [ 10 ]. This may help to promote more accurate and honest drug use self‐reporting.…”
Section: Discussionmentioning
confidence: 99%
“…The Avon Longitudinal Study of Parents and Children (ALSPAC), a large United Kingdom (UK) birth cohort, has a long‐standing relationship between participants and researchers. Participants report a high level of trust in the study [ 10 ], which may facilitate accurate reporting of illicit drug use. We compare illicit drug use data from the ALSPAC birth cohort with the population‐based household Crime Survey for England and Wales (CSEW).…”
Section: Introductionmentioning
confidence: 99%